What do scientist and non-scientist teachers notice about biology diagrams? - Topsakal, Unsal Umdu; Oversby, John (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
In the present study, we have explored an aspect of teachers' perceptions of biology diagrams. The research was performed in Turkey. The data were gathered from 50 (25 female, 25 male) teachers of primary and secondary schools and 34 (18 female, 16 male) academic staff of different universities in Turkey. Some of the participants are science specialists and the others are non-science specialists. The data were collected in 2012. A qualitative approach was adopted. The data were collected in three steps. First, biology diagrams from the internet were collected and some (12) biology diagrams were chosen by the researchers. In the second step, these selected diagrams were shown to the teachers and academic staff. In this step the participants were asked to think aloud about what they saw when they looked at the diagrams. In the third step, semi-structured interviews were carried out in order to examine further the thoughts of the participants about what they saw in these diagrams. In our study we found there were no significant differences in responses between the science and non-science specialist teachers and academic staff. We conclude that it may be helpful to train teachers in the processes of constructing and reading diagrams.
Keywords: diagrams; biology teaching; biology learning; Life Sciences & Biomedicine - Other Topics; Education & Educational Research